2019
DOI: 10.1111/asj.13253
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β (GSK3β) regulates the expression of MyHC2a in goat skeletal muscle satellite cells (SMSCs)

Abstract: Glycogen synthase kinase beta (GSK3β) plays an important role in skeletal muscle growth, regeneration, and repair. However, the mechanism of GSK3β regulating MyHC2a expression is currently not clear. In this study, GSK3β inhibition promoted skeletal muscle satellite cells (SMSCs) differentiation and increased expression of MyoD, MyoG, MyHC1, and MyHC2a genes. Then we cloned approximately 1.1 kb of goat MyHC2a gene promoter. The deletion fragment (−514/+55) of MyHC2a promoter exhibited the highest level of prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The attenuated increase of MyHC IIb mRNA in HS+A group may be caused by increased NFAT transcriptional activity, as it was shown that NFATc1 can repress MyHC IIb transcription (McCullagh et al, 2004). Partial prevention of MyHC IIa mRNA transcription decrease in HS+A group may be caused by NO-dependent GSK-3β inactivation, as it was shown that GSK-3β inhibition upregulates MyHC IIa in goat satellite cells (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The attenuated increase of MyHC IIb mRNA in HS+A group may be caused by increased NFAT transcriptional activity, as it was shown that NFATc1 can repress MyHC IIb transcription (McCullagh et al, 2004). Partial prevention of MyHC IIa mRNA transcription decrease in HS+A group may be caused by NO-dependent GSK-3β inactivation, as it was shown that GSK-3β inhibition upregulates MyHC IIa in goat satellite cells (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Both L-arginine administration and PMS during 7-day HS partially prevented downregulation of MyHC IIa mRNA transcription [ 66 , 114 ]. Previously it was shown that GSK-3β inhibition is able to upregulate the expression of slow myosin in chicken skeletal muscle [ 115 ] and MyHC IIa in goat satellite cells [ 116 ], however it is unclear why 3 days of PMS during unloading led to GSK-3β inhibition but did not activate MyHC IIa transcription in rat soleus muscle.…”
Section: Impact Of Gsk-3β Activity On Fiber-type Transitions and Oxidative Capacity In Skeletal Muscles Under Mechanical Unloading And Sumentioning
confidence: 99%
“…Studies have shown that the MSTN gene is a negative regulator of skeletal muscle growth and development and functions by controlling the number, size, and type of muscle fibers ( Bi et al, 2021 ). GSK3β regulates the expression of the MYHC-2A gene via NFATC2 to promote SMSC differentiation in goats ( Wang et al, 2019a ). The mTOR signaling pathway regulates the phosphorylation of myocyte enhancer factor 2 ( MEF2 ) through ILK , thereby affecting SMSC proliferation and differentiation ( Wu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%